3D Graphitic Foams Derived from Chloroaluminate Anion Intercalation for Ultrafast Aluminum‐Ion Battery. Issue 41 (29th August 2016) - Wu, Yingpeng; Gong, Ming; Lin, Meng‐Chang; Yuan, Chunze; Angell, Michael; Huang, Lu; Wang, Di‐Yan; Zhang, Xiaodong; Yang, Jiang; Hwang, Bing‐Joe; Dai, Hongjie
Abstract : A 3D graphitic foam vertically aligned graphitic structure and a low density of defects is derived through chloroaluminate anion intercalation of graphite followed by thermal expansion and electrochemical hydrogen evolution. Such aligned graphitic structure affords excellent Al‐ion battery characteristics with a discharge capacity of ≈60 mA h g −1 under a high charge and discharge current density of 12 000 mA g −1 over ≈4000 cycles.